Key issues in healthcare gamification research - Machado, Franklin Jean (2022)
The world is facing many health challenges related to high blood pressure, tobacco use, sedentarism, obesity and chronic stress. The mental health area deals with issues related to rising stress levels, anxiety, and depression. These problems seemed to get even worst within the pandemic context. In general, all health risks generated by modern lifestyles are a result of individual improper health behavior. Gamification can be applied to the healthcare scenario as a tool to engage people in healthier practices. Innumerous examples of these gamified initiatives exist, from mobile apps engaging people in exercising to meditation apps motivating users into daily mindfulness practices. Evidence of the effects of gamification in healthcare is also abundant but points to mixed interpretations. Literature indicates that a better comprehension of user behavior and characteristics might be valuable for developing more engaging gamified interventions. This thesis investigates healthcare gamification research, primarily focusing on assessing the behavior of users of gamified apps. To achieve this goal, we designed this research into three studies: the first develops a science map to reveal the healthcare gamification literature intellectual structure. The second applies quantitative techniques to investigate the behavior of users of the gamified meditation app Headspace. The third uses the clustering method to group Headspace users and profile them according to their use characteristics and verify how these characteristics might point out benefits potentially generated by the use of the gamified app. Through our investigation, we could identify and report the main traditions in healthcare gamification research, key themes researched and the most frequent adopted theories. We additionally found evidence of specific behavior intrinsic motivators of higher frequency and prolonged time of use of Headspace. Finally, we found higher levels of life satisfaction among a group of users that meditate with Headspace for higher frequencies and longer periods, suggesting a potential relationship between these variables.